Effect of instagram and celebrity endorser on purchasing motive of le minerale packaging water with image brand as intervention variables - Meitridasari, Utari; Wahab, Zakaria; Isnurhadi, Isnurhadi; Widiyanti, Marlina (International research journal of management, IT and social sciences, 2021)
This study aimed to analyze the effect of online marketing methods through Instagram and celebrity endorsers mediated by the brand image on purchase interest consumers of bottled drinking water under the Le Minerale brand produced by PT. Tirta Fresindo Jaya (Mayora Group). The data used are obtained from questionnaires given to respondents who have never been consuming a brand product. The collected data then analyzed using multiple linear regression with SPSS version 26 software. The results revealed that Instagram has a positive influence on Le Minerale's brand image. However, celebrity endorser does not show a positive influence on mineral water. Through the brand image, Instagram can have a positive influence on consumer buying interest, while the positive influence of celebrity endorser has made consumer purchase is more fantastic directly than currently mediated by brand image.